The Routledge handbook of pacifism and nonviolence - Fiala, Andrew G. 1966- (New York London Routledge, Taylor & Francis Group, 2018)
A history of the idea of pacifism and nonviolence : ancient to modern / Duane L. Cady -- Nonviolence and pacifism in the long 19th century / Michael Allan Fox -- Pacifism in the twentieth century and beyond / Andrew Fiala -- Christian pacifism / Daniel A. Dombrowski -- Peace and nonviolence in Islam / Ramin Jahanbegloo -- Philosophy of nonviolence in Africa / Gail M. Presbey -- Nonviolence in the Dharma traditions : Hinduism, Jainism, and Buddhism / Veena R. Howard -- The Gandhi-King tradition and satyagraha / Barry L. Gan -- Pacifism and the concept of morality / Robert L. Holmes -- Peace : negative and positive / David Boersema -- The pacifist critique of the just war tradition / Cheyney Ryan -- Contingent pacifism / Paul Morrow -- Humanitarian intervention and the problem of genocide and atrocity / Jennifer Kling -- Virtue ethics and nonviolence / David K. Chan -- Personal pacifism and conscientious objection / Eric Reitan -- Pacifism : does it make moral sense? / Jan Narveson -- Pacifism as pathology / José-Antonio Orosco -- The triumph of the liberal democratic peace and the dangers of its success / Fuat Gursozlu -- Human rights and international law / Robert Paul Churchill -- Hospitality, identity, and cosmopolitanism : antidotes to the violence of otherness / Eddy M. Souffrant -- Warism and the dominant worldview / Duane L. Cady -- The military-industrial complex / William Gay -- Feminism and nonviolent activism / Danielle Poe -- Queer oppression and pacifism / Blake Hereth -- Care theory, peace making, and education / Nel Noddings -- Becoming nonviolent : sociobiological, neurophysiological, and spiritual perspectives / Andrew Fitz-Gibbon -- The death penalty and nonviolence : justice beyond empathy / Lloyd Steffen -- Ecology and pacifism / Mark Woods -- Animals, vegetarianism, and nonviolence / Christopher Chapple -- Children, violence, and nonviolence / Jane Hall Fitz-Gibbon -- Peace pedagogy from the borderlines / Renee Bricker, Yi Deng, Donna Gessell, and Michael Proulx -- Afterword : nonviolence and the non-existent country / James M. Lawson, Jr
Afterword : nonviolence and the non-existent country James M. Lawson, Jr
Literaturangaben
Keywords: Pacifism; Nonviolence; Pazifismus; Gewaltlosigkeit; Gewaltverzicht; Politische Philosophie; Krieg; Friede; Theorie; Handbuch; Aufsatzsammlung